August Henry Mouns’s trip to Kartli - Nikoleishvili, Otar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
The history of Georgia, its contemporary existence, and its diverse nature have always been a subject of special interest to people visiting us from different countries. Proof of this can be considered the fact that most of the travelers who came to our country were not only satisfied with the sight of big cities but also tried to visit certain parts of Georgia. In order to clarify what has been said, this time I would like to pay special attention to the information provided about Georgia by the British diplomat - Augustus Henry Mounsey (Augustus Henry Mounsey, 1834–1882). A. H. Moons entered Georgia, in particular Poti, in December 1865 from Constantinople. From here he headed to Tbilisi. In mid-January 1866, he traveled first to Yerevan and then to Persia. His travel impressions of that time are described in his book A Journey Through the Caucasus and the Interior of Persia, published in London in 1872. Although a. H. Mouns’s book does not provide a detailed description of Kartli as one of the most important regions of our country and its constituent cities, and the author provides information about them only as a result of narration of various situational episodes, this paper should still be considered as one of the most important written documents in this regard. The fact that it is a hitherto unexplored historical source by Georgian researchers especially increases the interest in the mentioned work.